Beyond Free Will: Variety in Understanding of Choice, Luck, and Necessity - Beinorius, Audrius; Berniūnas, Renatas; Dranseika, Vilius; Rimkevičius, Paulius; Silius, Vytis; Veisaitė, Agnė (Vilnius University Proceedings, 2022)
Contemporary Western discourse on freedom and choice – some of the most championed modern values – is usually anchored in the concept cluster of free will and autonomous choice. In turn, academic research on free will in philosophy (including experimental philosophy) and psychology is largely based on a limited conceptual framework with roots in particular debates in Christianity and European philosophy. This framework is currently challenged by multidisciplinary and interdisciplinary approaches applied in the fields of area and Asian studies, comparative philosophy, and also empirical research in cross-cultural psychology, and anthropology. One reason for this challenge is that the dominant Western academic approach, with its almost exclusive focus on concepts of free will and causal determinism, neglects the multitude of non-Western cultural traditions. In most parts of the world, these traditions continue to shape everyday practices and conceptualizations of free action, choice, and decision. Traditions also provide various strategies for navigating the constraints on human agency. In the present multidisciplinary and interdisciplinary conference, we invited scholars from philosophy, psychology, anthropology, Asian studies, religious studies and other related fields to discuss theoretical alternatives to the dominant framework that are sensitive to cultural differences and local contexts as well as empirical research – especially crosscultural and cross-linguistic – on conceptualizations of free and constrained action and cultural practices in dealing with these constraints. This project “Between choice and determinism: cultural variations in experiencing and conceptualizing free will, luck and randomness” has received funding from European Social Fund (project No. 09.3.3-LMT-K-712-01-0111) under grant agreement with the Research Council of Lithuania (LMTLT).